Exploring the Associations between Sleep Problems and Chronic Musculoskeletal Pain in Adolescents: A Prospective Cohort Study - Lee Harrison; Sue Wilson; Marcus R Munafò (Pain Research and Management)
BACKGROUND: The prevalence of musculoskeletal chronic pain in adolescents is estimated to be approximately 4% to 40%. The development of musculoskeletal pain during teenage years could have a marked impact on physical, psychological and social well-being.